SiC Fiber 강화 다공질 반응소결 탄화규소 Composite 의 제조 및 기계적 특성 - 한재호; 박상환 (한국세라믹학회, 2006)
were developed by using Si melt infiltration process. The porosity and average pore size in fabricated chopped SiC fiber reinforcedporous RBSC composites were in the range of 30~40% and 40-90m, which mainly determined by the SiC powder size used asstarting material and amount of residual Si in porous composites. The maximum flexural strength of chopped SiC fiber reinforcedporous RBSC composite was as high as 80 MPa. The delayed fracture behavior was observed in chopped SiC fiber reinforced porousRBSC composites upon 3-point bending strength test.